2004
DOI: 10.1007/s10329-004-0110-z
|View full text |Cite
|
Sign up to set email alerts
|

How does stone-tool use emerge? Introduction of stones and nuts to na�ve chimpanzees in captivity

Abstract: Nut-cracking behavior has been reported in several communities in West Africa but not in East and Central Africa. Furthermore, even within nut-cracking communities, there are individuals who do not acquire the skill. The present study aimed to clarify the cognitive capability required for nut-cracking behavior and the process through which the the nut-cracking behavior emerges. To examine emergence, we provided three naive adult chimpanzees with a single opportunity to observe human models. A human tester demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Similarly, Hayashi et al [32] reported that already on the first day of observing a human cracking macadamia nuts, two of three human-reared chimpanzees placed a nut on an anvil stone and hammered it, with one succeeding on that day and the second on the next session. This is again consistent with social learning, yet there was no baseline or other control condition reported, weakening the strength of the evidence.…”
Section: Experimental Studies Of Nut-cracking By Chimpanzees (A) Backmentioning
confidence: 99%
“…Similarly, Hayashi et al [32] reported that already on the first day of observing a human cracking macadamia nuts, two of three human-reared chimpanzees placed a nut on an anvil stone and hammered it, with one succeeding on that day and the second on the next session. This is again consistent with social learning, yet there was no baseline or other control condition reported, weakening the strength of the evidence.…”
Section: Experimental Studies Of Nut-cracking By Chimpanzees (A) Backmentioning
confidence: 99%
“…Understanding how we learn from others has been of interest to psychologists for over a century (Baldwin 1902;Rogers & Williams 2006), and during this time it has been investigated by a range of disciplines including anthropology, cognitive neuroscience, robotics and philosophy, as well as developmental, social and comparative psychology ( Dautenhahn & Nehaniv 2002;Meltzoff & Prinz 2002;Want & Harris 2002;Frith & Wolpert 2003;Bekkering et al 2005;Breazeal et al 2005;Hayashi et al 2005;Hurley & Chater 2005;Kubota 2005;Lukowski et al 2005). Research into children's social learning is undergoing a major expansion, stimulated in part by the integration of developmental and comparative perspectives ( Want & Harris 2002;Call et al 2005;Carpenter et al 2005;Tomasello et al 2005;Horner et al 2006;Tennie et al 2006;McGuigan et al 2007), which has allowed the distinction of social learning processes from the simple, such as local or stimulus enhancement, to the complex, including imitation and goal emulation.…”
Section: Introductionmentioning
confidence: 99%
“…Captive studies have similarly shown the effectiveness of a skilled demonstrator, whether it be a human model [Sumita et al, 1985;Hayashi et al, 2005;Hirata et al, 2009] or a proficient conspecific [Sumita et al, 1985;Marshall-Pescini and Whiten, 2008;Hirata et al, 2009]. Additionally, interindividual variation in acquisition of these skills that is present in wild populations is evident among captive chimpanzees as well.…”
Section: Introductionmentioning
confidence: 91%
“…In order to succeed at cracking nuts, individuals must be able to order objects hierarchically in both space and time [Matsuzawa, 1996], inhibit their focus towards food in order to find and combine tools [Sumita et al, 1985;Hayashi et al, 2005], understand the force necessary to break open a nut, and understand the size and weight differences needed for one tool to be a hammer and another an anvil [Bril et al, 2009]. In the wild, nut cracking is variable between cultural groups as well as individuals [Matsuzawa, 1994;McGrew et al, 1997;Hayashi et al, 2005]. Chimpanzees in separate communities crack distinct species of nuts and use different materials for anvils, even though the same nuts and tools are available to both communities.…”
Section: Introductionmentioning
confidence: 99%